2021
DOI: 10.3389/fimmu.2021.651033
|View full text |Cite
|
Sign up to set email alerts
|

Immune Landscape of Gastric Carcinoma Tumor Microenvironment Identifies a Peritoneal Relapse Relevant Immune Signature

Abstract: BackgroundGastric cancer (GC) still represents the third leading cause of cancer-related death worldwide. Peritoneal relapse (PR) is the most frequent metastasis occurring among patients with advanced gastric cancer. Increasingly more evidence have clarified the tumor immune microenvironment (TIME) may predict survival and have clinical significance in GC. However, tumor-transcriptomics based immune signatures derived from immune profiling have not been established for predicting the peritoneal recurrence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 84 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…In the emerging immunotherapy strategies such as the ICB therapy in various types of cancer, the interaction of tumor DNA damage and repair landscape with patient immune system and related therapy has recently been revealed as a complex biological process ( Fridman et al, 2012 ; Gentles et al, 2015 ; Mouw et al, 2017 ; Bever and Le, 2018 ; Joshi and Badgwell, 2021 ; Zhang et al, 2021 ). Nevertheless, many prognostic and predictive biomarkers are being evaluated clinically to identify criteria for establishing customized therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In the emerging immunotherapy strategies such as the ICB therapy in various types of cancer, the interaction of tumor DNA damage and repair landscape with patient immune system and related therapy has recently been revealed as a complex biological process ( Fridman et al, 2012 ; Gentles et al, 2015 ; Mouw et al, 2017 ; Bever and Le, 2018 ; Joshi and Badgwell, 2021 ; Zhang et al, 2021 ). Nevertheless, many prognostic and predictive biomarkers are being evaluated clinically to identify criteria for establishing customized therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 27 reported a ten-immune-related gene signature with a 1-year AUC of 0.681 and even failed to reach 0.57 in the GSE15459 cohort and 0.559 in the GSE84437 cohort; these results are not acceptable. Zhang et al 28 reported an immune signature in the GSE62254 cohort, with an AUC value of only 0.793 in the entire cohort. Izumi et al 29 constructed a gene expression-based 15-gene signature to distinguish lymph node status and obtained an AUC value of only 0.829 in the GSE62254 cohort.…”
mentioning
confidence: 99%
“…Other groups have studied specific patterns of the TME to develop metabolic, 79 immune, 80 and collagen 81 signatures predictive of GCPM. In a more comprehensive, transcriptomewide analysis, a six-gene panel predictive of both synchronous and metachronous GCPM has been identified.…”
Section: Molecular Biomarkers Predictive Of Gcpmmentioning
confidence: 99%